Economic Impact of Restoration of Historic Pond in Bhaktapur - A Case Study of Bhaju Pukhu (Journal of Science and Engineering, 2026)
Bhaktapur, a city with several UNESCO World heritage sites, is known for its rich cultural legacy, traditional architecture and water management system, which include multiple medieval ponds. These historical ponds, which were originally essential to the city’s ancient water system and cultural life has been neglected, polluted and encroached upon for decades. Recent restoration projects seek to restore its historical relevance, enhance community well-being, and contribute to sustainable urban development. This study focuses on urban implications of culturally significant pond in Bhaktapur, with particular emphasis on Bhaju Pukhu to better understand the economic impact of such projects. The restoration of historical ponds not only preserves cultural heritage but also provides tangible economic benefits to the neighbourhood. This case study explores the financial implications of restoring Bhaju Pukhu, a centuries-old pond in Bhaktapur, Nepal. The study finds that the project has made a considerable contribution to the local economy through field surveys, interviews with local stakeholders, and analysis of tourism and business activity before and after restoration. Key findings include increased number of visitors, growth in local business such as tea shops, fast food, local vendors, and higher property values in the surrounding area. Furthermore, the restored pond has become a place for cultural events and festivals, resulting in increased economic activity. Employment opportunities were created during and after the restoration process. The study indicates that heritage pond restoration, when carefully planned and supported by the community, can serve as a driver for long-term economic development in historic cities such as Bhaktapur.